The Effect of Price and Product Quality on Consumer Satisfaction and Repurchase Interest at Cipork Keriyuk (Cab. G-Walk) - Ongkowijoyo, Thenie Elzae (Universitas Ciputra Surabaya, 2022)
Cipork Keriyuk is a restaurant that offers food with pork based in Surabaya. This food is currently famous among the culinary trends in Indonesia. During this Pandemic Covid-19 Cipork continues to grow and strives to survive in the tight competition of the food business. Product quality and price are important factors that determine customer satisfaction, especially for those culinary businesses. Customer satisfaction also can affect the repurchase intention of customers. Cipork Keriyuk doesn’t rule out the possibility of complaints and disappointments from customers. This research aims to find out whether this is the influence of product quality and price on customer satisfaction and repurchase intention on the study on Cipork Keriyuk Gwalk Branch. This research uses a quantitative method with sampling technique purposive sample. Primary data is collected by spreading a questionnaire to every customer that has consumed Cipork with a total amount unknown. The analysis technique used is SEM (Structural Equation Modeling) with PLS (Partial Least Square) for the data analysis method. The result of this research is that price and product quality are significant influences on customer satisfaction and repurchase intention, but customer satisfaction does not have a significant effect on repurchase intention.